SYSTEMATIC LITERATURE REVIEW : KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MODEL PROBLEM BASED LEARNING (PBL) BERPENDEKATAN STEM - Udin, Muhammad Rifa Udin; Zaenuri Masturi; Walid (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2025)
The purpose of this article is to explain the relationship between the PBL learning model and students' problem solving abilities using a STEM approach. The method used in this article is a systematic literature review (SLR). A systematic literature review is carried out by searching various written sources originating from books, articles and journals, or documents that are relevant to the problem being studied. This research used 14 articles that met the inclusion criteria, namely with research subjects of middle school - high school students, meeting syntax 1-4 and between 2015 and 2023. These articles were searched using national and international journal databases, namely Google Scholar, Researchgate, Scopus and Science Direct . This article concludes that the ability of middle school or high school students when solving a problem increases after implementing the PBL learning model with a STEM approach. The next recommendation for researchers is to dig deeper into the use of the PBL model and its consequences in problem solving at a further level with a different approach.